Migrants and the urban regeneration of Rockey/Raleigh high street in Yeoville: a case for a successful planning for diversity in inner-city of Johannesburg - Dala Diana, Fleury (My University, 2009)
The aim of this research report is to assess the extent to which the City of Johannesburg is implementing the inner-city regeneration process with regard to social inclusion in this era of migration. The research is motivated by the current trend in planning which emphasizes the need to overcome the issue of diversity. Planners aim to contribute to create cities where human and social capital is pooled to pull the city out of decay and where different people from different cultural and historical backgrounds come to live together. The research focuses on the case-study of Rockey/Raleigh High Street, the business hub in the suburban inner-city area of Yeoville. The area has been chosen because it is characterised by a high level of diversity and it is where migrant owners of all sorts of SMMEs trade. The research has collected data through interviews conducted with migrant business owners and representatives of the Yeoville Stakeholder Forum (YSF), the city agency JDA and the inner-city Forum. It has also used secondary data from survey research done by the University of the Witwatersrand, Tufts University and the French Institute of South Africa. The findings of the research have been analyzed through the lens of planning theory and the criteria of mainly qualitative and quantitative methods. They show that the CoJ’s commitment to urban regeneration that serves to celebrate and build on the diversity of social inclusion of the migrants in the inner city is less significant. The research recommends the strengthening of the relationships between the city council, the citizen action group and the migrants of Yeoville, the review of the conception of urban regeneration by the City Council and the building of social capital by the migrants.